Essential Oils as Alternative Promising Anti-Candidal Agents: Progress and Prospects - Shala, Awad; Singh, Shweta; Hameed, Saif; Khurana, S.M. P. (Current Pharmaceutical Design, 2022)
Candida albicans is one of the main agents responsible for opportunistic pathogenic infections. The progressive emergence of fungal resistance to conventional antibiotics and its side effects, as well as treatment costs, are considered major limitations for antifungal drugs. It has drawn scientists' attention to the search for potential substitution and reliable therapeutic alternatives for the antifungal compounds from sources like medicinal plants, which contain numerous bioactive compounds such as essential oils. Essential oils (EO), apart from having lower toxicity and better biodegradability, are eco-friendly in nature as compared with conventional antibiotics. Furthermore, extracted essential oils have been reported to possess potent antimicrobial, antiinflammatory, and antioxidant properties that nominate them as promising natural candidates to combat numerous fungal ailments. Thus, the determination of antifungal efficacy of essential oil-bearing plants on Candida spp. will provide miscellaneous knowledge for future clinical studies that are required for the development of new formulations as alternative therapeutic agents to control the growth of Candida species. Therefore, this review summarizes the gist of major essential oils that have been investigated for their anti- Candida potential with some recommendations for further study.
Keywords: cytotoxicity